2014
DOI: 10.1371/journal.pone.0093377
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Dextrose and Lipopolysaccharide on the Corrosion Behavior of a Ti-6Al-4V Alloy with a Smooth Surface or Treated with Double-Acid-Etching

Abstract: Diabetes and infections are associated with a high risk of implant failure. However, the effects of such conditions on the electrochemical stability of titanium materials remain unclear. This study evaluated the corrosion behavior of a Ti-6Al-4V alloy, with a smooth surface or conditioned by double-acid-etching, in simulated body fluid with different concentrations of dextrose and lipopolysaccharide. For the electrochemical assay, the open-circuit-potential, electrochemical impedance spectroscopy, and potentio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 55 publications
1
22
0
Order By: Relevance
“…The Vickers hardness was measured by means of an indenter (Shimadzu, HMV-2 Micro Hardness Tester, Shimadzu Corporation, Kyoto, Japan) by the application of a 0.5 Kgf load for 15 s. The test was performed in five samples of each group at four randomly distributed points [32]. The mean was calculated for each sample and then for each group to obtain the hardness (expressed in Vickers hardness units-VHN).…”
Section: Mechanical Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The Vickers hardness was measured by means of an indenter (Shimadzu, HMV-2 Micro Hardness Tester, Shimadzu Corporation, Kyoto, Japan) by the application of a 0.5 Kgf load for 15 s. The test was performed in five samples of each group at four randomly distributed points [32]. The mean was calculated for each sample and then for each group to obtain the hardness (expressed in Vickers hardness units-VHN).…”
Section: Mechanical Propertiesmentioning
confidence: 99%
“…The surface roughness parameters (average roughness, Ra; maximum height of the profile, Rt; average maximum height of the profile, Rz; and root mean square roughness, Rq) of the samples were evaluated by profilometry (Dektak 150-d; Veeco, Plainview, NY, USA). The roughness parameters were obtained with a cut-off of 0.25 mm at 0.05 mm/s over 12 s. Three measurements (right, center, and left of the sample) were obtained from five discs of each group and then averaged [32].…”
Section: Surface Characterizationmentioning
confidence: 99%
“…As a result, cells of the osteoblastic lineage are attracted more quickly and effectively, especially to regions of lower bone tissue density [6,7]. Combining the favorable characteristics of microstructural and biological behavioral aspects is a concern related to this range of texturing options [3][4][5], because the literature has shown that some of these methods alter titanium mechanical strength, electrochemical behavior, and bone healing responses [7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…These surfaces are achieved by means of double acid etching, which appears to have the potential to greatly enhance osseointegration without adding particulate matter or embedding surface contaminants [18]. The biological [18,19] and corrosion behaviors [20] of this type of surface have been evaluated when applied in cpTi and Ti-Al-V alloys. However, the effect of such etching treatment on promising Ti-Zr alloys with different Zr concentrations has not yet been studied.…”
Section: Introductionmentioning
confidence: 99%